Harnessing windfall revenues: optimal policies for resource-rich developing economies - Van der Ploeg, R (University of Oxford, 2011)
A windfall of natural resource revenue (or foreign aid) faces government with choices of how to manage public debt, investment, and the distribution of funds for consumption, particularly if the windfall is both anticipated and temporary. Standard policy advice follows the permanent income hypothesis in suggesting a sustained increase in consumption supported by interest on accumulated foreign assets (a Sovereign Wealth Fund) once resource revenue are exhausted. However, this strategy is not optimal for capital-scarce developing economies. Incremental consumption should be skewed towards present generations, relative to those in the far future. Savings should be directed to accumulation of domestic private and public capital rather than foreign assets. Optimal policy depends on instruments available to government. We study cases where the government can make lump-sum transfers to consumers; where such transfers are impossible so optimal policy involves cutting distortionary taxation in order to raise investment and wages; and where Ricardian consumers can borrow against future revenues so government only has indirect control of consumption.